2004
DOI: 10.1093/toxsci/kfh207
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Thalidomide on Developmental, Peri- and Postnatal Function in Female New Zealand White Rabbits and Offspring

Abstract: The present study determined effects of thalidomide on three successive generations of New Zealand White rabbits after oral dosing to F0 maternal rabbits during the later third of gestation (post major organogenesis) and lactation. One hundred and twenty four time-mated F0 rabbits (31/dose) were gavaged with 0, 30, 150, or 500 mg/kg thalidomide from gestation day 18 (DG 18) to lactation day 28 (DP or day postpartum 28) for approximately 42 days. At 6 months, 12 F1 males and 12 F1 females were randomly paired w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 42 publications
0
11
0
Order By: Relevance
“…In particular, in the absence of any detected direct adverse effects of this dosage on the does, selective effects on development were identified including postimplantation loss, reduced live litter size, reduced fetal body weight, and multiple fetal malformations and variations, some of which were previously identified for thalidomide (Somers, 1962;Nudleman and Travill, 1971;Teo et al, 2004).…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…In particular, in the absence of any detected direct adverse effects of this dosage on the does, selective effects on development were identified including postimplantation loss, reduced live litter size, reduced fetal body weight, and multiple fetal malformations and variations, some of which were previously identified for thalidomide (Somers, 1962;Nudleman and Travill, 1971;Teo et al, 2004).…”
Section: Discussionmentioning
confidence: 89%
“…Speciesselective teratogenicity of thalidomide is well established, and many animal species do not respond similarly to humans in which thalidomide produces limb defects (Schardein, 1985;Shepard, 1989;Neubert and Neubert, 1997). Rabbits are among the species that do show limb defects similar to those observed in humans (Somers, 1962;Nudleman and Travill, 1971;Schardein, 1985;Neubert and Neubert, 1997), and studies of thalidomide in rabbits have shown that it causes multiple endpoints of developmental toxicity, including congenital malformations, postimplantation losses, abortions, reduced fetal body weights, and decreased postnatal survival of pups (Hay, 1964;Fratta et al, 1965;Nudleman and Travill, 1971;Teo et al, 2004). However, most of these studies were conducted using rabbit strains with small or no historic databases, relatively few animals, and were academic in nature, i.e., designed to identify the mechanism of action by which limb malformations were induced.…”
Section: Introductionmentioning
confidence: 99%
“…Notably, thalidomide elicited highly variable responses in the many animal species studied. In primates and a few strains of rabbits severe congenital malformations (as described above for humans) were reported, but only moderate effects were found in rats and no significant changes were observed in mice (Fratta et al, 1965;Schumacher et al, 1968;Teo et al, 2001Teo et al, , 2004. For this reason, transcriptomic studies on thalidomide have mainly used human ESCs (hESCs) (Mayshar et al, 2011;Meganathan et al, 2012).…”
Section: Contents Lists Available At Sciencedirectmentioning
confidence: 99%
“…In primates and a few strains of rabbits severe congenital malformations similar to humans were reported, but only moderate effects were found in rats and no significant changes were observed in mice (Fratta et al, 1965;Schumacher et al, 1968;Teo et al, 2001Teo et al, , 2004. The reason for mouse insensitivity to thalidomide is not well understood.…”
Section: Tablementioning
confidence: 99%
“…Thalidomide exists in two enantiomeric forms, the ( R )- and ( S )-isomers which cause the differences in its biological activity. While the enantiomers can interconvert (racemize) in vivo [86], their pathogenic mechanisms are still not understood. Recently, thalidomide has been considered as a potential drug for various diseases such as autoimmune diseases, AIDS, Hansen’s disease, and some cancers [87, 88].…”
Section: Dna Aptamers For Pharmaceuticalsmentioning
confidence: 99%